Gender inequalities in caries experience among primary school-children. A cross-sectional study in a rural area of Indonesia - Sri Widiati; Al. Supartinah Santoso (Journal of Global Pharma Technology, 2020)
OBJECTIVES Dental caries is known as one of the most prevalent chronic diseases among school-children, especially those with lower socioeconomic status and higher sugar consumption. The purpose of the study is to compare caries prevalence between female and male school-children aged 11-13 years, adjusting for socioeconomic status. METHODS A cross-sectional study was carried out in a rural area of Sleman, Indonesia, to estimate the effect of gender, parental education and family income. A sample of 1,144 children at fifth grade were selected from 45 elementary schools in Sleman, Indonesia. Information concerning paternal education, demographic data of the school-children and family income were obtained from parents or guardians of the children. Caries status (DMF-T) of the schoolchildren was examined according to WHO dental health survey guidelines. RESULTS The results of the study showed that female students had on average 0.39 higher DMF-T than male students (p=0.001) and 28% less odds for caries-free status (p=0.009) adjusting for paternal education and family income. University education of fathers was associated with 0.53 lower DMF-T compared to the lowest education category and 79% increase in odds for caries-free status. There is no difference in restorative index between male and female students reflecting similar experience in dental care. CONCLUSIONS Female school-children aged 11-13 years were consistently at a greater risk for dental caries adjusting for parental education, an issue for further research and school-based oral health promotion program.